2022
DOI: 10.30714/j-ebr.2022173855
|View full text |Cite
|
Sign up to set email alerts
|

The association between postoperative corneal edema and phacoemulsification level

Abstract: To evaluate the effect of phacoemulsification level on postoperative central corneal thickness (CCT) differences and to assess the effects of demographic characteristics, biometric values and surgical parameters of patients on postoperative corneal edema. Methods: This prospective study included 232 eyes of 232 patients who underwent phacoemulsification surgery. Biometric values, phacoemulsification time, phacoemulsification power and effective phacoemulsification time (EPT) were evaluated. CCT measurements we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…A recent study has also found that more anterior planes than the capsular bag increase corneal edema and that this edema can last for more than a week [ 15 ]. Furthermore, studies assessing the effect of the phaco tip position on endothelial cell loss have discussed which tip position keeps the ultrasound energy far from the endothelium and brings the PP closer to the capsular bag [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has also found that more anterior planes than the capsular bag increase corneal edema and that this edema can last for more than a week [ 15 ]. Furthermore, studies assessing the effect of the phaco tip position on endothelial cell loss have discussed which tip position keeps the ultrasound energy far from the endothelium and brings the PP closer to the capsular bag [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%